2015
DOI: 10.1093/occmed/kqv089
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chronic embitterment among NHS staff

Abstract: Although the data are cross-sectional and self-reported, they provide evidence of the burden on organizations of chronic embitterment among their staff, particularly in terms of sickness absence. Staff who are embittered perceive their organization as unsupportive of them, and as showing low levels of procedural justice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…With regards to what predicts chronic embitterment in the workplace, the present findings are consistent with Sensky's et al, (2015) who reported an association between workplace embitterment and procedure justice, and further supports Linden's (2003) arguments that embitterment is mainly attributed to the individual's experience of injustice or unfairness. However, the present findings specifically suggest that perceived unfairness, because of structural and organisational aspects, significantly predict feelings of embitterment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With regards to what predicts chronic embitterment in the workplace, the present findings are consistent with Sensky's et al, (2015) who reported an association between workplace embitterment and procedure justice, and further supports Linden's (2003) arguments that embitterment is mainly attributed to the individual's experience of injustice or unfairness. However, the present findings specifically suggest that perceived unfairness, because of structural and organisational aspects, significantly predict feelings of embitterment.…”
Section: Discussionsupporting
confidence: 90%
“…Sensky, Salimu, Ballard, and Pereira (2015) have indeed provided some initial support to this position, as they found that employees who experience embitterment in their workplace report experiencing low levels of procedural justice. However, Sensky et al (2015) focused only on one aspect of organisational justice.…”
Section: Introductionmentioning
confidence: 93%
“…Situations reported are often characterized by perceived interpersonal injustice, missing social support or disloyalty (Sensky, Salimu, Ballard & Pereira, 2015). In military health research, embitterment has been discussed along with the concept of moral injury (Bryan, 2016).…”
Section: Posttraumatic Disorders and Work Capacity Impairmentmentioning
confidence: 99%
“…Embitterment at work has also been found to be associated with sickness absence (Sensky et al, 2015).…”
Section: Posttraumatic Disorders and Work Capacity Impairmentmentioning
confidence: 99%
“…A cross-sectional study on chronic embitterment among occupational health professionals showed that embittered staff perceived their organization as being unsupportive and characterized by low levels of procedural justice. 17 People who are embittered typically feel victimized, experience resentment and injustice, resist help, and have difficulty coping. 18 Decreasing embitterment encourages positive beliefs, assists survivors in perceiving others as being supportive, and promotes help-seeking.…”
Section: Discussionmentioning
confidence: 99%